48.9k views
20 votes
5x + 3(1 – 2) = 2(x – 3) + 5

User Jimijazz
by
4.9k points

2 Answers

8 votes

Answer:

x= 2/3

Explanation:

User Shreeram Bhat
by
5.2k points
10 votes

Answer:

x = 2/3 or 0.66666666666

Explanation:

Ok Andy heres what u do

5x + 3(1 – 2) = 2(x – 3) + 5 ---> ur gonna use substitution for this one

5x + 3 - 6 = 2x - 6 + 5 ---> equation should look like this after

since u have extra numbers on both sides left just add or subtract them

5x - 3 = 2x - 1 ---> now this would be ur final equation so all u have to do is solve!

5x - 3 = 2x - 1

+ 3 = 2x + 3

--------------------- ---> add 3 on both sides

5x = 2x + 2

- 2x = - 2x + 2

----------------------- ---> subtract 2x on both sides

3x = 2

now u just do 2 ÷ 3 which equals 0.66666666666 or if u want ur answer to be in fraction then just leave it as 2/3 so do u get it now?

User Yaser Kalali
by
5.4k points